2021
DOI: 10.1021/acs.chemmater.1c00061
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Onset of Metal–Insulator Transitions in Transition Metal Oxides—A First Step in Designing Neuromorphic Devices

Abstract: Several transition metal oxides, including La1–x Sr x CoO3, are promising materials to realize resistive switching devices for neuromorphic applications, as they can undergo a metal-to-insulator transition (MIT) upon small perturbations to their electronic structure. Here, we focus on the MIT induced by varying the oxygen vacancy concentration, and we propose a model to predict the required electrical bias, based on three fundamental quantities: the vacancy formation energy, the permanent polarization in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…V th drops from at least 2.4 to 3.0 V at x = 0 (where the upward arrow indicates that long-range BM order was not detected in SXRD) to negligible at x = 0.70. Below, we discuss specific conclusions regarding the origin of the overall decrease in V th with x and its apparent nonmonotonicity in Figure ; for now, we note only that V th is clearly doping-tunable, a feature that would appear attractive for applications such as neuromorphic computing. , , …”
Section: Resultsmentioning
confidence: 99%
“…V th drops from at least 2.4 to 3.0 V at x = 0 (where the upward arrow indicates that long-range BM order was not detected in SXRD) to negligible at x = 0.70. Below, we discuss specific conclusions regarding the origin of the overall decrease in V th with x and its apparent nonmonotonicity in Figure ; for now, we note only that V th is clearly doping-tunable, a feature that would appear attractive for applications such as neuromorphic computing. , , …”
Section: Resultsmentioning
confidence: 99%
“… 1 5 The phase transformation between brownmillerite and perovskite is enabled by applying an electric-field even at room temperature owing to the low oxygen vacancy formation energy and the high oxygen vacancy diffusivity of such systems. 24 , 25…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: controlling oxygen vacancies in vanadates, 44 doping rare-earth nickelates (e.g., SmNiO 3 ) with light ions such as hydrogen, 45 and controlling vacancies and doping in LaCoO 3 . 46 Due to their high mobility, the distribution of light ions or ion vacancies is sensitive to short voltage pulses, enabling controllable tuning of neuromorphic device resistance. Memory nano-devices based on this effect are promising candidates for artificial neuromorphic synapses.…”
Section: A Metal-insulator Transitions In Quantum Materialsmentioning
confidence: 99%
“…Zhang and Galli recently elucidated the impact of oxygen vacancies on the structural, electronic, and magnetic changes responsible for the metal-insulator transition in cobaltites. 46 Interestingly, they showed that cooperative structural distortions, rather than local bonding changes, are responsible for the gap closing.…”
Section: A Metal-insulator Transitions In Quantum Materialsmentioning
confidence: 99%